Review of nanosheet transistors technology - Agha, Firas N. A. Hassan; Naif, Yasir H.; Shakib, Mohammed Nazmus (Tikrit University, 2021)
Nano-sheet transistor can be defined as a stacked horizontally gate surrounding the channel on all direction. This new structure is earning extremely attention from research to cope the restriction of current Fin Field Effect Transistor (FinFET) structure. To further understand the characteristics of nano-sheet transistors, this paper presents a review of this new nano-structure of Metal Oxide Semiconductor Field Effect Transistor (MOSFET), this new device that consists of a metal gate material. Lateral nano-sheet FET is now targeting for 3nm Complementary MOS (CMOS) technology node. In this review, the structure and characteristics of Nano-Sheet FET (NSFET), FinFET and NanoWire FET (NWFET) under 5nm technology node are presented and compared. According to the comparison, the NSFET shows to be more impregnable to mismatch in ON current than NWFET. Furthermore, as comparing with other nano-dimensional transistors, the NSFET has the superior control of gate all-around structures, also the NWFET realize lower mismatch in sub threshold slope (SS) and drain induced barrier lowering (DIBL).